Bridging global goals with local realities: university engagement with the SDGs in Pakistan - Cheema, Abdur Rehman; Ahmed, N.; Hassan, H.; Kemal, M. A. (Taylor & Francis, 2025)
Universities are where global promises meet local problems. This study examines how Pakistan’s higher education sector is aligning with the Sustainable Development Goals (SDGs) across four domains—learning and teaching, research, governance and external leadership—based on responses from 41 of 247 universities. We find energetic activity in SDG—related teaching and research, but slower movement on institutional governance and outward leadership. Engagement varies by place: provincial and regional priorities mirror local socio—economic and environmental realities, from poverty and education to water, energy and climate resilience. Common barriers persist—limited funding, weak institutionalisation of SDGs and scarce incentives for interdisciplinary collaboration. Yet the potential is clear: universities already catalyse practical, localised solutions and can do more by embedding SDGs in curricula and operations, investing in partnerships with government, industry and communities and expanding student—led initiatives. The paper offers evidence, lessons and policy directions to help align campus capabilities with national and global sustainability ambitions.